Evaluasi Primer Gen COI sebagai Biomarker Ketertelusuran Ikan menggunakan Bioinformatika: Evaluation of COI Gene Primer as a Biomarker Traceability using Bioinformatics - Nugraha, Roni; Dewi, Puspita Sari; Nurilmala, Mala (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Traceability is carried out to provide information for tracking fish species, especially of high economic value and vulnerable to extinction. Bioinformatics can predict biomarker for fish traceability. This study was aimed to evaluate widely used primer sequences of COI gene for fish traceability and identify new universal primer sequences. Primers used in previous researches were evaluated and aligned with 33 fish species sequences from the NCBI GenBank. The relationship of those 33 fish species was evaluated using Percent Identity Matrix (PIM) and phylogenetic trees. The results showed not all primers have a good quality. CO1shark25 and CO1shark315 primer can be aligned to 31-32 fish sequences but did not fulfilled the ideal primer parameters. Therefore, several new universal primers were designed that fit the ideal criteria. The primer was designed and evaluated by using PerlPrimer and OligoEvaluator software. Fish universal mini-barcode primers from Lagocephalus lagocephalus, Takifugu vermicularis, Arothron hispidus, Hypanus americanus, Isurus oxyrhyncus, and Katsuwonus pelamis sequences successfully designed and evaluated for alternative biomarkers.